2011
DOI: 10.1371/journal.pone.0024505
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Efficacy and Safety of Experimental Vaccines Based on Non-Replicating Vaccinia Vectors against Yellow Fever

Abstract: BackgroundCurrently existing yellow fever (YF) vaccines are based on the live attenuated yellow fever virus 17D strain (YFV-17D). Although, a good safety profile was historically attributed to the 17D vaccine, serious adverse events have been reported, making the development of a safer, more modern vaccine desirable.Methodology/Principal FindingsA gene encoding the precursor of the membrane and envelope (prME) protein of the YFV-17D strain was inserted into the non-replicating modified vaccinia virus Ankara an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
0
22
0
3
Order By: Relevance
“…A potentially safer Vero cell-derived inactivated vaccine was evaluated in phase I clinical trial (Monath et al, 2011). Candidate experimental vaccines also include NS1 protein vaccine (Schlesinger et al, 1986), as well as the modified vaccinia Ankara and the D4R-defective vaccinia viruses expressing 17D prME protein (Schafer et al, 2011). In this study, we configured recently developed iDNA® approach (Tretyakova et al, 2014; Tretyakova et al, 2013) to prepare a novel experimental vaccine for YFV.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially safer Vero cell-derived inactivated vaccine was evaluated in phase I clinical trial (Monath et al, 2011). Candidate experimental vaccines also include NS1 protein vaccine (Schlesinger et al, 1986), as well as the modified vaccinia Ankara and the D4R-defective vaccinia viruses expressing 17D prME protein (Schafer et al, 2011). In this study, we configured recently developed iDNA® approach (Tretyakova et al, 2014; Tretyakova et al, 2013) to prepare a novel experimental vaccine for YFV.…”
Section: Discussionmentioning
confidence: 99%
“…8K). The discrepancy between downregulation of MHC-I and that of MHC-II may provide an indication of why recombinant MVA induces stronger CD8 ϩ than CD4 ϩ T cell responses (4,67) (Fig. 4 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of YFV antigens by live-attenuated, recombinant vaccinia constructs was shown to be feasible in the late 1990s[73]. A recent effort used the replication-deficient modified vaccinia virus Ankara (MVA) and d4R defective vaccinia virus (dVV) to vector the 17D prM/M-E antigen protected mice from intracerebral challenge with 17D when administered in a single dose (17D substrains, though highly attenuated in humans, are virulent for mice when directly introduced to the brain) [74]. The study not only demonstrated protection and immunogenicity of the constructs, but also high apparent safety in mice, as the vaccines themselves were not neurotropic when administered at doses exceeding the that required to induce protection.…”
Section: New Yfv Vaccine Candidate Technologies and Monitoring Of Safetymentioning
confidence: 99%